Vishnu with a maiden offering flowers - 025 - Saurabh Saxena (2022)
Image courtesy : Saurabh Saxena - https://puratattva.in/ Though the maiden here is at times identified as Lakshmi, there are no attributes to confirm that. Also, in the Hoysala temples Lakshmi is usually portrayed as significantly as Vishnu - next to him or sitting on his lap.